Individually Weighted-Average Models: Testing a Taxonomic SEM Approach Across Different Multidimensional/Global Constructs Because the Weights "Don't Make No Nevermind". Issue 1 (2nd January 2018) - Marsh, Herbert W.; Scalas, L. Francesca
Abstract : From the time of William James, psychologists have posited individually importance-weighted-average models (IWAMs) in which weighting specific attributes by individual measures of importance improves prediction of the global outcome measures. Because IWAMs cause much confusion, we briefly review a general taxonomic paradigm and structural equation models for testing IWAMs, and demonstrate its application for 2 simulated and 3 diverse "real" data applications (multidimensional measures of self-concept, quality of life, and job satisfaction). Consistent across the real data applications and previous research more generally, there is surprisingly little support for IWAMs when tested appropriately. In these diverse tests of IWAMs we integrate new approaches such as exploratory structural equation modeling (SEM), alternative approaches to constructing latent interactions, application of bifactor models, modeling method and item-wording effects, and the juxtaposition of model evaluation in relation to goodness of fit (typically used in SEM studies) and variance explained (typically used in multiple regression tests of IWAMs).